ChemInform Abstract: Smart Drug Delivery Nanocarriers with Self‐Assembled DNA Nanostructures. Issue 46 (24th October 2013) - Li, Jiang; Fan, Chunhai; Pei, Hao; Shi, Jiye; Huang, Qing
Abstract Review: 110 refs.